Bulk Polymerization Kinetics of Hydroxy Terminated Polybutadiene and Toluene Diisocyanate with Infrared Spectroscopy - Heri Budi Wibowo; Widhi Cahyo; Ratih Sanggra (Universitas Gadjah Mada, 2018)
A study on bulk polymerization kinetics of HTPB (Hydroxy Terminated Polybutadiene) and TDI (Toluene Diisocyanate) with infrared (IR) spectroscopy has been conducted. The investigations included the molar ratio of 2,4-TDI to 2,6-TDI isomers, the initial molar ratio of isocyanate group to a hydroxyl group, and the reaction temperature. The polymerization rate constant was calculated based on the decrease rate of TDI. Kinetics model had been evaluated through the following reaction steps: (1) 2,4-urethane production, (2) 2,6-urethane production, (3) the reaction between 2,4-urethane and the isocyanate group of 2,4-TDI, (4) the reaction between 2,4-urethane and the isocyanate group of 2,4-TDI, (5) the reaction between 2,6-urethane and isocyanate group of 2,4-TDI, and (6) the reaction between 2,6-urethane and the isocyanate group of 2,6-TDI. Those reaction steps were assumed to be the first order reaction with the reaction rate constants k1, k2, k3, k4, k5, and k6, respectively. The reaction rate constants obtained at molar ratio of 2,4-TDI to 2,6-TDI of 80:20, isocyanate group to hydroxyl group (RNCO/OH) initial molar ratio of 1:1, and reaction temperature of 40 °C were 6.2 × 10-5, 5.8 × 10-5, 3.1 × 10-5, 2.8 × 10-5, and 2.5 × 10-5 L.mole-1.min-1 for k1, k2, k3, k4, k5, and k6, respectively, with the activation energy of 1152, 952, 1001, 656, and 1001 kJ/mole for reaction (1)–(6), respectively. The results show that the polymerization reaction rate-determining step was the reaction of 2,6-urethane and isocyanate group of 2,6-TDI (reaction (6)).